Deficiencies in one-carbon metabolism led to increased neurological disease risk and worse outcome: homocysteine is a marker of disease state - Joshi, Sanika M.; Jadavji, Nafisa M. (Frontiers in Nutrition, 2024)
Elevated plasma homocysteine levels have been identified as a significant, independent risk factor for the development of cognitive decline including Alzheimer's disease. While several studies have explored the link between homocysteine and disease risk, the associations have not been entirely clear. Elevated levels of homocysteine serve as a disease marker and understanding the underlying cause of these increased levels (e.g., dietary or genetic deficiency in one-carbon metabolism, 1C) will provide valuable insights into neurological disease risk and outcomes. Previous cell culture experiments investigating the mechanisms involved used ultra-high levels of homocysteine that are not observed in human patients. These studies have demonstrated the negative impacts of ultra-high levels of homocysteine can have on for example proliferation of neuroprogenitor cells in the adult hippocampus, as well as triggering neuronal apoptosis through a series of events, including DNA damage, PARP activation, NAD depletion, mitochondrial dysfunction, and oxidative stress. The aim of this minireview article will summarize the literature on deficiencies in 1C and how they contribute to disease risk and outcomes and that homocysteine is a marker of disease.